The Hundred Years War: England and France at war c.1300-c.1450 - Allmand, Christopher (Cambridge Cambridge University Press, 1988)
This is a comparative study of how the societies of late-medieval England and France reacted to the long period of conflict between them commonly known as the Hundred Years War. Beginning with an analysis of contemporary views regarding the war. Two chapters follow which describe the military aim of the protagonists, military and naval organisation, recruitment, and the raising of taxes. The remainder of the book describes and analyses some of the main social and economic effects of war upon society, the growth of a sense of national consciousness in time of conflict, and the social criticism which came from those who reacted to changes and development brought about by war. Although intended primarily as a textbook for students, Dr Allmand's study is much more than that. It makes an important general contribution to the history of war in medieval times, and opens up new and original perspectives on a familiar topic
Keywords: Middle Ages (500-1400); Hundred Years' War (1337-1453); United Kingdom; France